2016
DOI: 10.1128/iai.00694-16
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii Avirulent Nine Mile Phase II Induces Caspase-1-Dependent Pyroptosis in Murine Peritoneal B1a B Cells

Abstract: Our recent study demonstrated that virulentCoxiella burnetiiNine Mile phase I (NMI) is capable of infecting and replicating within peritoneal B1a cells and that B1a cells play an important role in host defense againstC. burnetiiinfection in mice. However, it remains unknown if avirulent Nine Mile phase II (NMII) can infect and replicate in B1a cells and whether NMI and NMII can differentially interact with B1a cells. In this study, we examined if NMI and NMII can differentially modulate host cell apoptotic sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 66 publications
(75 reference statements)
1
14
1
Order By: Relevance
“…In contrast, our recent studies found that NMII can induce apoptosis in undifferentiated THP-1 cells through a caspase-3-independent pathway (22). We also found that NMII-infected murine peritoneal B1a cells undergo caspase-1-dependent pyroptosis through activation of Toll-like receptor 2 and NLRP3 signaling pathways (23). However, it remains unclear whether C. burnetii can modulate neutrophil apoptosis.…”
contrasting
confidence: 56%
“…In contrast, our recent studies found that NMII can induce apoptosis in undifferentiated THP-1 cells through a caspase-3-independent pathway (22). We also found that NMII-infected murine peritoneal B1a cells undergo caspase-1-dependent pyroptosis through activation of Toll-like receptor 2 and NLRP3 signaling pathways (23). However, it remains unclear whether C. burnetii can modulate neutrophil apoptosis.…”
contrasting
confidence: 56%
“…In the present study, results showed that B-1 and B-2 cells deficiency in XID mice together with cyclophosphamide treatment caused a more severe and spread encephalitozoonosis, which was similar the described to SCID and nude mice [28]. B-1 cells have phagocytic and microbicide capabilities [29] and are considered very important in the defense against Coxiella burnetti , by its ability to produce antibodies, cytokines and promote phagocytosis [30]. The lack of B cells increased the susceptibility of CBA/XID to Cryptococcus neoformans disseminated fungal disease [31].…”
Section: Discussionsupporting
confidence: 68%
“…Pyroptosis is characterized by rapid plasma membrane rupture and the release of proinflammatory intracellular contents and is morphologically and mechanistically distinct from other forms of cell death. [33][34][35][36][37] Several studies have indicated that pyroptosis contributes to infectious diseases, nervous system disorders, and atherosclerosis. [38][39][40] Pyroptosis is sometimes followed by the induction of inflammasome formation, which is also pathogenic for the development of renal tissue damages in IR injuries.…”
Section: The Effects Of Foxo3 Knockdown On B-ohb Mediated Anti-pyroptmentioning
confidence: 99%